2019
DOI: 10.1037/prj0000341
|View full text |Cite
|
Sign up to set email alerts
|

“It suits my needs”: Self-employed individuals with psychiatric disabilities and small businesses.

Abstract: Objective: Small business is a favorably regarded institution in America. Given employment disparities among individuals with psychiatric disabilities compared to other workers, self-employment has potential to promote career development and community integration. However, little is known about what has helped or hindered current small business owners with psychiatric disabilities. This exploratory study identified characteristics of individuals' work and disability histories, as well as business characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…However, some groups are more vulnerable than others, both in the labour market and socially. People with mental illness are the group with the highest unemployment, and as many in this group have experienced discrimination, this is a common motive among them for starting their own business (Ostrow et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some groups are more vulnerable than others, both in the labour market and socially. People with mental illness are the group with the highest unemployment, and as many in this group have experienced discrimination, this is a common motive among them for starting their own business (Ostrow et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This review has shown that avoiding discrimination is another motive for starting one's own business. Discrimination is accounted for either by analysing statistics on participants in the labour force collected via labour market surveys (Gouskova 2020;Jones and Latreille 2011), or empirically by noting individuals' experiences of discriminating employers, colleagues, and clients (Maritz and Laferriere 2016;Ostrow et al 2019;Quinton 2014). However, few studies have tested the role of discrimination in their research questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most people with schizophrenia have unskilled jobs, such as laboring, manufacturing, or sales/service. Although this may be due to social bias, it also appears to be a result of the disorder becoming chronic, in addition to schizophrenia's characteristic symptoms [44].…”
Section: Discussionmentioning
confidence: 99%
“…The articles address traditional employer-employee relationships as well as the relationships developed when people with disabilities choose to create and manage flexible work arrangements that they own and operate, as self-and independent contractors do. The flexibility of such arrangements is one reason that a relatively high proportion of people with disabilities engage in self-employment and independent contracting relationships in the new "gig" economy rather than pursuing (or continuing to pursue) traditional employment [27,28].…”
Section: Contributions To This Special Topic Sectionmentioning
confidence: 99%